PENGARUH PELATIHAN DAN MOTIVASI TERHADAP PERODUKTIVITAS KERJA KARYAWAN - Sylvia Kristinauli Siregar Siagian; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to determine the effect of training and motivation on the work productivity of the employees of the PT Prima Medica Nusantara Hospital in Tebing Tinggi, either partially or simultaneously. This study uses primary data and a sample of 42 respondents. The results of the study prove that training has no effect partially, this is evidenced by 0.840 <2.023 with a significance value of 0.406> 0.05. Meanwhile, motivation has a partial effect on work productivity with evidence of 5.424> 2.023 with a significance value of 0.00 <0.05. And simultaneously training and motivation have a significant effect on work productivity with proof that is 20.20> 3.24 with a significance value of 0.00 <0.05.